Water Policy, Productivity and Economic Efficiency (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Over the past few decades, water policies have undergone significant changes in many countries, notably due to the development of national and international political, social, and environmental issues, including globalization, trade liberalization, institutional and legal requirements, changing standards of living, management practices, and technological innovation. Policy changes include both "high level" views about water status and practical instruments, in particular with an emphasis on integrated basin management and economic policy instruments. A relevant part of the water policy literature addresses this topic, mainly as an issue related to environmental conservation. However, water remains a major productive factor, particularly in agriculture. This role is made even more prominent in light of economic crises, increased competition across markets and climate change, as well as fossil energy limitations, which also highlight the water-energy nexus as a key resource issue for future economic viability. The delay, in the past, in recognizing the economic consequences of a limited water supply, and in decoupling economic development from water demand and supply, has resulted in a water-dependent growth model, currently threatened by increasing scarcity and droughts. Consequently, there is now an urgent need for new perspectives for promoting a more sustainable and efficient use of water resources. This calls for, on the one hand, a comprehensive understanding of water efficiency and productivity and, on the other hand, an investigation of the linkages among economic sectors to illustrate trade-offs in water reallocations. In addition, this also points to the need to study the institutional innovations and economic evaluation instruments that are able to better assess policy performance and provide evidence for improved mechanism designs aimed specifically at water efficiency and productivity.